What can Nature-based Solutions in domestic gardens contribute to climate change adaption in Western-Europe? a systematic review - Teerlinck, Janne; Wittemans, Kelly; Beele, Eva; Dewaelheyns, Valerie; Steen, Trui; Somers, Ben (Frontiers in Environmental Science, 2024)
Research has shown that the collective network of domestic gardens could make a substantial contribution to climate change adaptation. One way to harness this contribution is by implementing Nature-Based Solutions (NBS). However, due to the predominant focus on NBS applicable in large-scale and publicly available urban green areas, there is a lack of comprehensive research encompassing NBS specifically applicable to domestic gardens and their associated ecosystem services. Through a systematic review following the ROSES protocol, this paper provides an overview of the existing knowledge on small-scale NBS and climate resilient gardening practices, as well as, identifies research needs. This work contributes to the growing recognition of the spatial and ecological importance of domestic gardens for climate adaptation, and stresses the urgent need for more quantitative research on the range and effectiveness of ecosystem services provided by small-scale NBS. In this paper, we reflect upon the feasibility and practical implications of three specific NBS: the improvement of current lawn management practices, the reduction of sealed soil or pavement present, and the integration of trees in domestic gardens. We also acknowledge the potential of Citizen Science and governmental initiatives to engage citizens and improve the adoption of NBS in domestic gardens. Our work highlights the additional benefits and crucial role of urban planning and policy in integrating domestic gardens into broader climate adaptation strategies.